Ribonucleotides embedded in template DNA impair mitochondrial RNA polymerase progression. Issue 2 (8th January 2022) - Singh, Meenakshi; Posse, Viktor; Peter, Bradley; Falkenberg, Maria; Gustafsson, Claes M
Abstract: Human mitochondria lack ribonucleotide excision repair pathways, causing misincorporated ribonucleotides (rNMPs) to remain embedded in the mitochondrial genome. Previous studies have demonstrated that human mitochondrial DNA polymerase γ can bypass a single rNMP, but that longer stretches of rNMPs present an obstacle to mitochondrial DNA replication. Whether embedded rNMPs also affect mitochondrial transcription has not been addressed. Here we demonstrate that mitochondrial RNA polymerase elongation activity is affected by a single, embedded rNMP in the template strand. The effect is aggravated at stretches with two or more consecutive rNMPs in a row and cannot be overcome by addition of the mitochondrial transcription elongation factor TEFM. Our findings lead us to suggest that impaired transcription may be of functional relevance in genetic disorders associated with imbalanced nucleotide pools and higher levels of embedded rNMPs. Graphical Abstract: